Discipline in Education Some less frequently explored issues - van der Walt, Johannes (NWU Education and Human Rights in Diversity Series, 2021)
This book addresses a perennial challenge to the success of the South African education system, namely, discipline. This volume steers the interrogation of discipline in a new direction, reflecting on ways in which recent research can benefit South African schools. This includes the need for alternative discipline that will enhance education. The scholarly contribution lies in its in-depth exploration of the relevance of research findings to South African schools and to the twenty-first-century socio-political environment. For the first time, scholarly interrogation of the issue of learner discipline in South African schools draws on indigenous knowledge systems. Its post-colonial and decolonial perspectives offer an ethical and moral compass for behaviour that could contribute to the well-being of South African society (and other societies similarly afflicted by anti-social behaviour). The book offers a range of perspectives on the debates on discipline and associated issues, and should stimulate future discussions on discipline and indiscipline at a time when South Africa and many other societies engage with the effects of social and political transformation. This scholarly book is aimed at academics and researchers. The contributors include philosophers, moralists, corporativists, education law specialists, curriculum specialists, specialists in education and culture, advocates of ubuntu, and people using meta-syntheses of approaches and practices and religious practices such as a Christian ethical/moral approach to parental and school discipline. They draw on their insights into postcolonialism, the impact of indigenous knowledge, theories of agency, dysfunctionality and school underperformance. The book offers an intriguing depiction of opposing views on discipline.